2010
DOI: 10.3109/13693780903501689
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus sequence typing of sequentialCandida albicansisolates from patients with persistent or recurrent fungemia

Abstract: Multilocus sequence typing (MLST) is a useful tool to explore the phylogenetics and epidemiology of Candida albicans isolates recovered from cases of invasive candidiasis. The goal of this study was to determine whether the same or different strains were responsible for persistent or recurrent fungemia through the use of MLST and ABC typing on sequential C. albicans isolates from the same patient. We applied both typing methods to 21 C. albicans strains recovered from 8 patients with persistent or recurrent ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 26 publications
1
28
1
Order By: Relevance
“…MLST is a powerful and useful technique for understanding the epidemiological and evolutionary relationships of pathogenic micro-organisms (Taylor & Fisher, 2003;Urwin & Maiden, 2003;Maiden, 2006;Cliff et al, 2008;Odds & Jacobsen, 2008;Da Matta et al, 2010;Shin et al, 2011). Prevalence of C. albicans infections in the BICU of the Zare hospital (Sari, Iran) led us to investigate the epidemiological relationship of 30 isolates involved using the MLST method.…”
Section: Discussionmentioning
confidence: 99%
“…MLST is a powerful and useful technique for understanding the epidemiological and evolutionary relationships of pathogenic micro-organisms (Taylor & Fisher, 2003;Urwin & Maiden, 2003;Maiden, 2006;Cliff et al, 2008;Odds & Jacobsen, 2008;Da Matta et al, 2010;Shin et al, 2011). Prevalence of C. albicans infections in the BICU of the Zare hospital (Sari, Iran) led us to investigate the epidemiological relationship of 30 isolates involved using the MLST method.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been developed to analyze microevolution and structure of C. albicans species. Although MLST (MultiLocus Sequence Typing) has been chosen as the most discriminatory technique [5,32], several articles have recently pointed towards the suitability of MLP [14-16,29]. In this study, nine isolates from a case of recurrent urinary infection were genotyped using microsatellites and a new HRM analysis method.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent and/or persistent infections by Candida species are frequent, particularly in oropharyngeal and vaginal candidiasis, although it has also been described in urinary tract infections [2]. Studies describing recurrent infections have focused on determining the relatedness between colonizing and infective strains [3,4], as well as between successive infective strains [5-9]. It seems clear now that the majority of commensal and infecting populations of C .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with invasive candidiasis might have complications such as endocarditis, abscesses, or chronic-disseminated candidiasis. Previous studies have reported that persistent fungemia is one of the complications found in patients with candidemia, occurring in over 10% of the patients (Da Matta et al, 2010). Some studies have shown that the immune response can influence the infection, comorbidities, and efficacy of pharmacologic therapy of patients with invasive candidiasis (Garey et al, 2006).…”
Section: Introductionmentioning
confidence: 99%